Polemic of Mudik in Indonesia: How People Deal with Government Regulation Related to Covid-19 - Tantri Agra Liz; Waluyo Sukarjo (E3S Web of Conferences, 2021)
Indonesia has a variety of cultures and traditions that develop in society; one of them is mudik, or the tradition of returning to hometown after a month of fasting during Ramadan to celebrate Eid al-Fitr. This tradition is an example of Indonesia's religious, cultural system related to the migration movement from one area to another. For many people, especially Muslims, mudik (homecoming) is considered an important event. However, since Covid-19 has been occurring globally, the government decided to ban this traditional annual activity, and it causes pros and cons to society. This research is intended to analyze society’s responses toward government regulation about the prohibition of mudik (homecoming) in 2021 due to Covid-19. Researchers used a quantitative descriptive method, namely utilizing data obtained through an online simple random sampling survey conducted on several Muslims and supported by literature studies. The result shows 64% of the respondents decided to follow the government regulation by not returning home this year. Based on the result, the existence of this (Addendum) Circular Letter of the Covid-19 Handling Task Force No.13, 2021 became a preventive way to restrain society from returning home for Eid al-Fitr this year.